IMPLEMENTATION OF THE TRANSLATION METHOD IN IMPROVING CHILDREN’S BASIC ENGLISH GRAMMAR MASTERY - Moch. Wahyudi Utomo; Muhammad Faizin (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
English serves as a pivotal medium for global scientific communication, necessitating early exposure to its structural foundations. In the context of pedagogical training, students of the Islamic Education Management (MPI) Study Program are tasked with bridging the gap between theoretical grammar and practical instruction for young learners. This study investigates the implementation of the Grammar-Translation Method (GTM) as a strategic tool used by MPI students to enhance basic English grammar mastery among children. The translation method is employed as a scaffolding technique, where students facilitate the translation of simple texts to foster accuracy and conceptual clarity in young learners’ grammatical understanding. This research adopts a qualitative case study approach, documenting the instructional practices of MPI students. Data were gathered through structured questionnaires and reflective observations distributed via digital platforms, capturing the students' experiences in adapting complex linguistic rules into digestible content for children. The findings indicate that the translation method significantly aids MPI students in delivering structured grammar lessons, resulting in improved comprehension and reading engagement among the children. Furthermore, the results suggest that this method not only strengthens the children’s linguistic foundation but also hones the pedagogical competence of MPI students in managing language-based educational programs. This study contributes to the development of effective teaching models within Islamic education frameworks, emphasizing the dual benefit of grammar mastery for both the instructor and the young learner.